A new anaerobic fungus (Oontomyces anksri gen. nov., sp. nov.) from the digestive tract of the Indian camel (Camelus dromedarius). Issue 8 (August 2015) - Dagar, Sumit S.; Kumar, Sanjay; Griffith, Gareth W.; Edwards, Joan E.; Callaghan, Tony M.; Singh, Rameshwar; Nagpal, Ashok K.; Puniya, Anil K.
Abstract: Two cultures of anaerobic fungi were isolated from the forestomach of an Indian camel ( Camelus dromedarius ). Phylogenetic analysis using both the internal transcribed spacer (ITS) and large-subunit (LSU) regions of the rRNA locus demonstrated that these isolates were identical and formed a distinct clade within the anaerobic fungi (phylum Neocallimastigomycota). Morphological examination showed that these fungi formed monocentric thalli with filamentous rhizoids and uniflagellate zoospores, broadly similar to members of the genus Piromyces . However, distinctive morphological features were observed, notably the pinching of the cytoplasm in the sporangiophore and the formation of intercalary rhizoidal swellings. Since genetic analyses demonstrated this fungus was only distantly related to Piromyces spp. and closer to the polycentric Anaeromyces clade, we have assigned it to a new genus and species Oontomyces anksri gen. nov., sp. nov. Interrogation of the GenBank database identified several closely related ITS sequences, which were all environmental sequences obtained from camels, raising the possibility that this fungus may be specific to camelids. Graphical abstract: Highlights: Two Neocallimastigomycota cultures were obtained from camel forestomach. Cultures were monocentric and formed uniflagellate zoospores. ITS and LSU sequence analysis placed these in a distinct clade close to Anaeromyces . Environmental sequences also from camel also fell into this clade. This new fungus is formally named Oontomyces anksri gen. nov., sp. nov.